PERBEDAAN KUANTITAS DAN KUALITAS HASIL JAHITAN UPPER SEPATU ANTARA MESIN JAHIT MANUAL DAN HIGH SPEED - Wawan Budi Setyawan (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2016)
This study aims to assess the differences in quantity and quality of the stitching on the manual sewing machine and high speed sewing machine and to know how much difference the use of manual sewing machine with high speed sewing machines. Data collected of this experimental study using measurement instruments and test documentation. Sample is determined based on purposive sampling and selected one student who made a shoe upper with manual sewing machine and a high speed sewing machine. Quantity was measured by suture completion time, while the quality is measured from the appearance of its sew, stitching distance precisely, sew wrinkle, and its good looking. The results showed no difference in quality and quantity of stitching of manual sewing machines and a high speed sewing machine. The magnitude of the difference in production using a sewing machine manual sewing machine high speed terms of the mean difference of 15. Manual sewing machine has the characteristics of more familiar than the high speed sewing machine. It’s easier than high speed sewing machine because it have lowerspeed so the operator can adjust easily, eventhough bout the quantity its more longer.